Epidemiology, Antimicrobial Resistance and β-lactamase Genotypic Features of Enteropathogenic Escherichia coli Isolated from Children with Diarrhea in Southern China - Huang, Yong; Shan, Xue-feng; Deng, Haijun; Huang, Yu-jun; Mu, Xiao-ping; Huang, Ai-long; Long, Quan-xin (Japanese Journal of Infectious Diseases, 2015)
The main objective of this study was to investigate the epidemiology, drug resistance and β-lactamase genotype distribution of enteropathogenic Escherichia coli (EPEC) isolated from pediatric patients with diarrhea in southern China. The prevalence of EPEC in children with diarrhea was 3.53%. The commonest serotypes were O55:K59 and O126:K71, and the typical EPEC were more prevalent than atypical EPEC (51 vs 7). Isolates from this region were most commonly found to be resistant to ampicillin and cotrimoxazole, followed by chloramphenicol, ceftriaxone, and ceftazidime. More than 96% of the strains were susceptible to cefoperazone/sulbactam and imipenem. The most common β-lactamase genotypes identified in 58 strains were blaCTX-M-1 (60.3%), blaTEM (56.9%), blaCTX-M-9 (27.6%), and blaSHV (15.5%). Among 58 isolates, 22 strains were found to harbor one β-lactamase gene, and the proportions of resistance to ampicillin, cotrimoxazole, chloramphenicol, ceftriaxone, and ceftazidime, were 81.8%, 63.6%, 40.9%, 18.2%, and 9.1%, respectively. A further 30 strains carrying multiple β-lactamase genes had increased resistance to the above antimicrobial agents (100%, 83.3%, 70.0%, 60.0%, and 30.0%, respectively). In contrast, antibiotic resistance in the last 6 strains without a detectable β-lactamase gene was substantially reduced. Drug resistance may be associated with the β-lactamase gene number, with a greater the number of β-lactamase genes resulting in higher antibiotic resistance.